Evaluation of Phytochemical and Antioxidant Properties of 15 Italian Olea europaea L. Cultivar Leaves - Nicolì, Francesca (Molecules, 2019)
Olive leaf extracts are of special interest due to their proven therapeutic effects. However, they are still considered a by-product of the table olive and the oil industries. In order to learn possible ways of exploiting this waste for health purposes, we investigated the phytochemical profiles and antioxidant activities in the leaves of 15 Italian Olea europaea L. cultivars grown in the same pedoclimatic conditions. The phenolic profiles and amounts of their seven representative compounds were analyzed using HPLC ESI/MS-TOF. The antioxidant activities were determined using three different antioxidant assays (DPPH, ORAC, and superoxide anion scavenging assay). Wide ranges of total phenolic content (11.39–48.62 g GAE kg(−1) dry weight) and antioxidant activities (DPPH values: 8.67–29.89 µmol TE mg(−1) dry weight, ORAC values: 0.81–4.25 µmol TE mg(−1) dry weight, superoxide anion scavenging activity values: 27.66–48.92 µmol TE mg(−1) dry weight) were found in the cultivars. In particular, the cultivars Itrana, Apollo, and Maurino, showed a high amount of total phenols and antioxidant activity, and therefore represent a suitable natural source of biological compounds for use in terms of health benefits.